Analisis Kerja Sama Perbatasan Pemerintah Thailand Melawan Human Trafficking Tahun 2018-2023 - Fazara Anggie Azarine; Renitha Dwi Hapsari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
In an era of increasing cross-border mobility, there is a significant impact on the security of a country and its people. The rise of transnational crimes such as human trafficking is a major threat to a country, as human trafficking involves forced recruitment, transportation, and exploitation, which are human rights violations. This research focuses on Thailand as a source, transit, and destination country for human trafficking, particularly with GMS countries such as Laos, Cambodia, and Myanmar. This study aims to assess the effectiveness of the Thai government's policies and the actions taken to combat human trafficking in terms of Henry Willis’ theory of border security policy from 2018 to 2023. This study employs a qualitative descriptive methodology focusing on 2018–2023. The report demonstrates Thailand's growing dedication to technological use and legal reform. However, inadequate interagency collaboration, corruption, and a lack of human resources hinder field implementation.